Association between time to therapeutic INR and length of stay following mechanical heart valve surgery. Issue 1 (18th October 2021) - Godoy, Lucas C.; Tomlinson, George; Abumuamar, Asmaa M.; Farkouh, Michael E.; Rudolph, Madeleine; Billia, Filio; Cohn, Iris; Marcus, Gil; Kim, Raymond H.; Rao, Vivek; Lawler, Patrick R.
Abstract: Background: Warfarin is the only oral anticoagulant approved for use following mechanical valve surgery (MeVS). Patients may experience prolonged hospital length of stay (LOS) following MeVS awaiting an appropriate warfarin effect. We aimed to determine whether an association exists between time to achieve the first therapeutic international normalized ratio (INR) and LOS following MeVS. Materials and Methods: Retrospective single center cohort study. We included consecutive adult patients undergoing elective MeVS from 2013 to 2018. Landmark analyses and multivariable regression with time‐updated INR were used to estimate the association between time to therapeutic INR (TTI) and LOS. Results: Among 384 patients (median age: 51 years, interquartile range [IQR]: 41–57; 58.3% male), the median TTI was 4 days (IQR: 2–5). Thirty seven percent of patients were discharged with a subtherapeutic INR, many on bridging anticoagulation or with an INR close to target. Those achieving therapeutic INR had an increased rate of hospital discharge (adjusted hazard ratio: 2.17; 95% confidence interval: 1.71–2.76; p < .0001). Attainment of a therapeutic INR anytime between postoperative Days 4 and 13 was significantly associated with a shorter LOS. Conclusions: Prolonged time to achieve a therapeutic INR was independently associated with prolonged LOS. Future strategies aimed at improving attainment of therapeutic INR following MeVS may reduce hospital LOS.